Effect of increasing proportions of lignocellulosic cosubstrate on the single-phase and two-phase digestion of readily biodegradable substrate. (September 2015) - Ganesh, Rangaraj; Torrijos, Michel; Sousbie, Philippe; Lugardon, Aurelien; Steyer, Jean Philippe; Delgenes, Jean Philippe
Abstract: The influence of different proportions of lignocellulosic substrate (cow manure with straw, CM) on the single-phase (conventional reactor) and two-phase (acidification/methanation with solids and liquid recirculation) digestion of a readily biodegradable substrate (fruit and vegetable waste, FVW) was investigated in order to determine the optimum cosubstrate ratio and the process best suited for codigestion. Both processes were fed initially with FVW, followed by FVW and CM at 80%:20% and 60%:40% (on volatile solids, VS basis) during an experiment run over eleven months. For the single-phase process, energy yield and VS destruction decreased by 11% and 9% with the 80%:20% FVW and CM ratio and by 16% and 17% with the 60%:40% feed ratio when compared to 100% FVW feed. For the two-phase process, energy yield and VS destruction decreased by 21% and 14% with 80%:20% feed ratio and by 48% and 33% with 60%:40% feed ratio compared to 100% FVW. Substrate solubilization in the acidification reactor was very efficient for all the feed proportions but it resulted in compounds other than volatile fatty acid (non-VFA COD) which were not easily amenable to methane generation. This led to a lower energy yield per kg of VS fed in the two-phase process compared to the single-phase process for the respective waste combination. For single-phase digestion, both 80%:20% and 60%:40% ratios were effective co-substrate combinations due to their higher energy yield. The two-phase process can be used for these ratios if higher VS reduction and a higher loading rate are the objectives. Highlights: Effect of cow manure addition on the digestion of fruit and vegetable waste studied. Single and two-phase processes were compared for three different waste ratios. Methane and energy yields were higher by single-phase than the two-phase process. FVW-Cow manure ratios of 80%:20% and 60%:40% found effective for single-phase digestion. Two-phase process resulted in higher solids removal and can be used for high loading rate operation.